Teoria da mente e autismo: influência da linguagem parental explicativa de estados mentais sobre o desenvolvimento da compreensão social - Gallo-Penna, Eliana Cristina (2012)
The manifestation of the Theory of Mind in autism is a singular issue, emphasized by the hypothesis that there are deficits in the ability of attributing mental states in autistic children, related to autism specific symptoms. This research is an experimental intervention, which aims to investigate the effects of a procedure, based on the ability of attributing mental states to others in autistic children. It is to guide mothers of autistic children to the use of children's stories telling based on the use of mental terms and explanations of mental states of desires, beliefs, intentions and emotions about the characters in order to foster the ability of understanding other people's mental states. Three children, ages 11 to 16, one boy and two girls students of regular schools from the state of Minas Gerais, participated of this research together with their mothers. The Theory of Mind was assessed in the pretest as well as the posttest, according to The Theory of Mind Scale. The intervention procedure lasted for six months. During this period, there were two group orientation plus fifteen individual ones. The individual orientations were held weekly in the children's homes, shortly after the children's stories telling. The stories, told by their mothers, were video recorded, transcribed and submitted to the SPAD - T software for treatment and categorization of terms of mental states attributing. The results showed that the language used for the mother, according to the guideline containing terms and explanations of mental states, was favoring the manifestation of the Theory of Mind for their children. It was observed in two children that there was a relationship between the mother's language and the performance of false belief tasks. It was observed an increase in the use of emotional terms in the children's speech, and in cognitive terms on the mother s lines. It is considered that the language is a predictor in attributing mental states to other people, also in autistic children. Children with better language skills can evoke mental terms, and are able to hit in the false belief tasks